Answer:
Step-by-step explanation:
Sorry this is a tough one and I don’t want to give you the wrong answers sorry again
First we will compute the h+k and then multiply the result by 2.
To add polynomials, we add terms whose variables are alike, for example:
we add the coefficients of x^2 together, the coefficients of x together and so on.
Therefore:
h + k = x^2 + 1 + x - 2 = x^2+x-1
Now, we will multiply this answer by 2 to get the final answer:
2(h+k) = 2(x^2+x-1) = 2x^2 + 2x -2
1.
f(x) = x
g(x) = x + 3
For each x value you use in f(x) and g(x), the corresponding y value in g(x) is always 3 more than in f(x). If each y-coordinate is 3 more, that means the graph is shifted 3 units up. The graph of f(x) is shifted 3 units up to create the graph of g(x).
2.
The first term is -0.5.
Then each term goes up by 0.25.
1st term: -0.5
2nd term: -0.5 + 0.25 = -0.5 + 0.25(1)
3rd term: -0.5 + 0.25 + 0.25 = -0.5 + 0.25(2)
4th term: -0.5 + 0.25 + 0.25 + 0.25 = -0.5 + 0.25(3)
nth term: -0.5 + 0.25(n - 1)
-0.5 + 0.25(n - 1) = -0.5 + 0.25n - 0.25 = -0.75 + 0.25n = 0.25n - 0.75
Answer is C.
Answer:
c
Step-by-step explanation: